A Meta-analysis of the Association between p53 Codon 72 Polymorphism and Susceptibility to Endometriosis. (August 2014) - Song, Gwan Gyu; Lee, Young Ho
Abstract : Objective : The aim of this study was to determine whether the p53 codon 72 polymorphism is associated with susceptibility to endometriosis. Methods : A meta-analysis was conducted on the associations between the p53 codon 72 polymorphism and endometriosis using 1) allele contrast, 2) a recessive model, 3) a dominant model, and 4) homozygote contrast. Results : Nine studies involving 1, 803 patients and 2, 006 controls were considered in the meta-analysis. Meta-analysis of the p53 polymorphism showed no association between endometriosis and the p53 C allele (odds ratio (OR) = 1.087, 95% confidence interval (CI) = 0.921–1.282, p = 0.323). Stratification by ethnicity indicated no association between the p53 C allele and endometriosis in Europeans and Latin Americans. However, a significant association was found between the p53 C allele and endometriosis in East Asians (OR = 1.405, 95% CI = 1.065–1.854, p = 0.016). Furthermore, association was found between the p53 polymorphism and endometriosis in East Asians using the dominant model (OR = 2.046, 95% CI = 1.123–3.730, p = 0.019). Conclusions: This meta-analysis demonstrates that the p53 codon 72 polymorphism may be associated with susceptibility to endometriosis in East Asians, but not in Europeans and Latin Americans.